Transformations of traditional land use and settlement patterns of Kosarysche Ridge (Chornohora, Western Ukraine) - Nowak Agnieszka; Tokarczyk Natalia (Bulletin of Geography. Socio-Economic Series)
The traditional character of Hutsul villages and their spatial development has been changing slowly but inevitably over the course of time. Historically, single farmsteads were built separately and were mostly self-sufficient, the distance between them being considerable. Nowadays, after the collapse of the Soviet Union, the economic transformation brought along many changes, among these the fact that depopulation is taking place and alterations in spatial development are occurring again. The localisation of secluded farmsteads, situated far away from each other is no longer as important as it used to be. Reasons for the abandonment of farmsteads were examined, and factors such as altitude, distance from the village centre and the administration affiliation were taken into account. Land use changes were analysed in relation to the slope inclination. Some of the most important factors influencing the intensity and direction of these processes are high prices of land, improvement in living conditions, better access to services and the general ‘westernisation’ of lifestyles. The depopulation rate has been seen to increase in correlation with the rising altitude and distance from the village centre. On the other hand, there was no unambiguous link between the abandonment of farmsteads and administration affiliation. Mowed areas were localised on the slopes with the smallest inclination. Animal breeding has become unprofitable due to a lack in demand and low product prices, which has led to an increasing number of meadows and pastures lying fallow.